The effect of dairy proteins on the oral burn of capsaicin. (12th December 2022) - Farah, Brigitte A.; Hayes, John E.; Coupland, John N.
Abstract: This study focused on the effect of binding of capsaicin by milk proteins on oral burn. The concentration of free, unbound capsaicin in 5 ppm capsaicin solution containing 0–5% (w/w) micellar casein or whey protein isolate was measured by extraction into hexadecane. The concentration of free capsaicin decreased linearly with protein concentration and the decrease was greater for casein than for whey protein. The intensity of the capsaicin burn in similar solutions was assessed by a large cohort (n = 89) of untrained participants in a time‐intensity study. The maximum burn intensity decreased with protein concentration and was lower for samples containing casein than for samples containing whey protein isolate. The maximum burn was linearly related to the free, unbound capsaicin concentration. When protein solutions (1–5% w/w) were used as rinses following exposure to a 5 ppm aqueous capsaicin solution, only the 5% (w/w) micellar casein solution was significantly more effective than the water rinse in reducing oral burn.